Faculty's Perceptions of Students' Characteristics: A for Effort Please - Sharon Stevens; Deb Miretzky (Arizona State University, 2012)
This pilot study explored how undergraduate students are perceived by higher education faculty regarding their initiative and abilities. Faculty tended to agree that students are engaged in class, but more specific skills and attitudes needed to perform successfully in college are not as apparent to them. Around half of faculty respondents with at least 10 years experience in higher education agreed these skills and abilities are declining. Emergent themes from comments suggest faculty believe students' skills and work ethic have declined while their sense of entitlement (e.g., to high grades) has increased. Comments also suggest faculty believe the decline is a result of a lack of preparation in basic skills from secondary school, the overall culture and politics of secondary education, students' unrealistic perceptions of the expectations in higher education, and students' active lifestyles outside of classes.